Performance of Ankle Exoskeletons on Irregular Terrains: Key Design Principles and Benchmarking Tests - L. Liguori; G. Mariani; J. Taborri; I. Mileti; D. Torricelli; L. Mattioli; E. Palermo; F. Patane; S. Rossi (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Exoskeletons offer an advanced solution for assisting and rehabilitating physically impaired people. The mechanical design of these devices can significantly affect the kinematics of the user by restricting limb movements. In this study, we present the mechanical design of two new prototypes of ankle exoskeleton with a different number of degrees-of-freedom (DoF) and different torque transmission method. Specifically, the first prototype (S-RANK) accommodates a single DoF in the sagittal plane, whereas the second prototype (M-RANK) extends the functionality to include ankle inversion/eversion and internal/external rotation. To assess the impact of the mechanical design of the exoskeletons on the kinematics of the lower limb, the two devices were donned on the right leg by two healthy subjects and tested on five different terrains. Human kinematics of the left and right lower limbs was collected using inertial measurement units (IMUs). The study assessed the effects on trend symmetry (TS) between the left and right limb kinematic parameters and used statistical parametric mapping (SPM) to compare joint angle curves with and without each prototype. The findings indicated that both prototypes exerted a notable influence on joint kinematics. The S-RANK resulted in a higher overall difference (OD), particularly at the ankle joint across all terrains except during downhill walking, with the largest deviations observed on softer surfaces. In contrast, M-RANK had a less pronounced effect on ankle kinematics but generally performed worse on the knee and hip joints. In these instances, it led to higher OD when walking on flat and softer surfaces. The two exoskeleton prototypes affected gait symmetry on all terrains, with S-RANK leading to a significant worsening on flat terrain. The findings indicate that while S-RANK offered stability and a less pronounced effect on proximal joint kinematics, M-RANK’s additional degrees of freedom provided superior adaptability and maintenance of natural gait patterns.